Ganoderma lucidum and Hypericum perforatum exhibit anti-inflammatory, antioxidant and anti-androgen effect in rat model of experimental polycystic ovarian syndrome - Okay, Gulin; Kirici, Pinar; Mavral, Nihal; Korun, Zeynep Ece Utkan; Annac, Ebru; Kaplan, Selcuk (Karger, 2024)
Objective: Chronic inflammation is considered to be of key importance in the pathogenesis of polycystic ovarian syndrome (PCOS). Ganoderma lucidum polysaccharide (GLP) and Hypericum perforatum (HP)have been reported to have anti-inflammatory and antioxidant activities. We studied the effects of these agents on ovarian tissue in a rat model of experimental PCOS. Materials and methods: Forty-two Sprague-Dawley female rats were divided into 6 groups with 7 animals in each group as listed below; Group 1: Control, Group 2: PCOS, Group 3: PCOS + HP, Group 4: HP only, Group 5: PCOS+ GLP, Group 6: GLP only. At the end of the experimental procedures, all animals underwent bilateral oophorectomy and blood samples were collected. Ovarian tissue and blood samples were used for biochemical and histopathological analysis. Results: Follicle degeneration in the PCOS group showed a statistically significant increase compared to the other groups (p<0.05). When the PCOS+GLP and PCOS+HP groups were examined, it was determined that the cystic follicles were significantly reduced compared to the PCOS group. Whereas tumor necrosis factor-alpha (TNF-a) and interleukin-6 (IL-6) levels were elevated in PCOS rats (p<0.01). Sex hormone binding globulin (SHBG) levels were diminished (p<0.01). MDA and IGF-1 levels were increased in PCOS rats as against the remaining groups (p<0.02, p<0.02, respectively). GLP supplementation to the treatment diminished IGF-1 and malondialdehyde (MDA). GLP or HP supplementation increased reduced glutathione (GSH). Conclusion: GLP and HP treatment normalizes SHBG levels while correcting PCOS-induced hyperandrogenemia. Both herbs regulate the redox balance by decreasing the MDA level and increasing the GSH.
Keywords: Activation